A Systematic Review of Foot Exercises with Group Support to Improve the Foot Health of Diabetes Mellitus Patients - Rohmatul Faizah; Ferry Efendi; Suprajitno Suprajitno (Universitas Airlangga, 2020)
Introduction: Foot problems are a process and complication in patients with diabetes mellitus (DM). Foot complications can be prevented by routine foot exercises. Group support is needed to increase the routine of foot exercise. The effects of foot exercise can be seen by measuring the Ankle Brachial Pressure Index and foot sensation. The objective of this systematic review was to identify the prevention of DM foot complications in an easy way so then he patient can do it independently.Methods: The method used in this study was a systematic review focused on 2015 – 2019 using the PRISMA method. The literature was obtained from Scopus, Science Direct and Proquest. The results found 25 items of literature on foot exercise which was reduced to 4 studies on preventing damage to the feet of DM patients through routine foot exercise. The literature of this study is supported by 3 other studies that state that foot health can also be used to examine the foot’s blood circulation status and sensation.Results: These results have been presented concerning 7 studies regarding special group support in the form of exercise therapy for patients with DM. This study explains the prevention of foot complications through foot exercise. Group support is needed provide motivation to conduct routine foot exercise.Conclusion: Foot exercise can accelerate the blood circulation as can be seen by the Ankle Brachial Pressure Index score and the increase in the neurological system of the foot through foot sensation status.